2019
DOI: 10.1212/wnl.0000000000008066
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal brain development in child and adolescent carriers of mutant huntingtin

Abstract: ObjectiveThe huntingtin gene is critical for the formation and differentiation of the CNS, which raises questions about the neurodevelopmental effect of CAG expansion mutations within this gene (mHTT) that cause Huntington disease (HD). We sought to test the hypothesis that child and adolescent carriers of mHTT exhibit different brain growth compared to peers without the mutation by conducting structural MRI in youth who are at risk for HD. We also explored whether the length of CAG expansion affects brain dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
99
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(114 citation statements)
references
References 45 publications
15
99
0
Order By: Relevance
“…Our current findings provide the first evidence for existing altered brain developmental processes at the system level in the heterozygous zQ175 KI HD model. In line with our observation in the human HD study ( van der Plas et al. 2019 ), these data indicate new aspects of the HD pathogenesis which is important to guide future therapeutic development.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our current findings provide the first evidence for existing altered brain developmental processes at the system level in the heterozygous zQ175 KI HD model. In line with our observation in the human HD study ( van der Plas et al. 2019 ), these data indicate new aspects of the HD pathogenesis which is important to guide future therapeutic development.…”
Section: Introductionsupporting
confidence: 87%
“…In line with these findings, we have recently reported significant brain region-selective developmental abnormalities in seventy-five child and adolescent carriers of mutant HTT ( van der Plas et al. 2019 ).…”
Section: Introductionsupporting
confidence: 79%
“…31 or Huntington's Disease. 32,33 These different trajectories are confirmed when observing the specific regions of decreased GM in the VBM analyses, and even allow for clearly showing that pediatric and adult/late onset patients display distinctive patterns of damage in a given time-spot and different trajectories from a longitudinal perspective. Specifically, pediatric DM1 patients showed reduced GM volume, mainly located at subcortical level at baseline, which additionally extended to cortical regions at followup, particularly the frontal lobe.…”
Section: Discussionmentioning
confidence: 65%
“…Overall, these findings suggest that HD, at least in its early-onset juvenile forms, may not be a purely neurodegenerative disorder and that abnormal neurodevelopment may be a component of its pathophysiology. This notion is further supported by several studies in children and adolescent HD gene carriers who are estimated to be decades from onset, showing altered intracranial volume [4] and brain region morphology [5,6].…”
Section: Increased Asymmetric Divisionmentioning
confidence: 64%
“…Moreover, the morphology of brain regions is substantially different in adult pre-manifest HD mutation carriers, with increased volume of the cerebral cortex and decreased volume of the basal ganglia and cerebral white matter [5]. A recent longitudinal study in children and adolescent HD gene carriers who were estimated to be on average 35 years from clinical onset revealed that an initial hypertrophy of striatal volume precedes the volume decline that develops with age [6]. Furthermore, two recent whole-exome sequencing studies have identified compound heterozygous variants in the HTT gene in patients with Rett-like syndrome, a neurodevelopmental disorder [7,8].…”
Section: Introductionmentioning
confidence: 99%